Efektivitas Alokasi Dana Desa dalam Meningkatkan Industri Kecil Menengah di Desa Kalukubula - Eka Ayu Setiawati; Yunus Sading; Kalvin A. Parinding; Eko Jokolelono; Nurnaningsih Nurnaningsih (Penerbit Goodwood, 2025)
Purpose: This study examines the extent of the utilization of village fund allocation to develop small and medium industries in Kalukubula village, Sigi Biromaru Sub-District. Method/approach: This study employs a qualitative method with a descriptive approach. Data collection techniques were carried out through observations, interviews, and documentation. The informants included village government officials and small-to medium-sized industry actors who received village fund support. This study applies Richard M. Steers' (1985) theory of Effectiveness, focusing on three indicators: goal achievement, adaptation, and integration. Results/findings: The results obtained by the author in this research show that the effective utilization of village funds enhances small and medium enterprises through support for business capital and equipment in Kalukubula Village, based on three indicators of effectiveness: achievement of goals, where support from village funds not only successfully increases community income but also creates business independence; adaptation by providing training facilities and offering assistance in infrastructure that meets the needs of entrepreneurs; and integration, where the Kalukubula Village Government has conducted socialization regarding the use of village funds. Conclusion: The allocation of village funds in Kalukubula Village has proven to be fairly effective in supporting the development of small and medium industries based on Steers' three organizational effectiveness indicators. Limitations: This research was limited by time and was only conducted in one village as a case study. Contribution: This study provides recommendations to the village government to maximize the use of village funds for the development of small and medium industries to improve the village economy.